Sleep matters: the U-shaped relationship between sleep duration and overactive bladder in U.S. adults - Guan, Ciyi; Wang, Lei; Wang, Chao; Ma, Yinhua; Chen, Yinjiao; Wu, Junjun; Pan, Hui; Zhang, Chang; Song, Haiyuan (Frontiers in Medicine, 2025)
ObjectivesTo investigate the independent and combined associations of sleep duration and sleep disorders with the risk of overactive bladder (OAB) and identify threshold effects of sleep duration on OAB.MethodsData from the NHANES (2005–2018) were analyzed, including 27,302 adults, among whom 5,601 (20.5%) were diagnosed with OAB. Associations between sleep duration (≤ 6 h, > 6 to < 9 h, ≥ 9 h), sleep disorders, and OAB risk were assessed using multivariable logistic regression, restricted cubic splines (RCS), and smooth curve fitting, adjusting for demographic, socioeconomic, lifestyle, and health-related covariates.ResultsA significant non-linear, U-shaped relationship between sleep duration and OAB risk was observed. Compared to individuals with a sleep duration of 6–9 h, those with short sleep duration (≤ 6 h) had a slightly lower risk of OAB (OR = 0.94), while those with long sleep duration (≥ 9 h) had a significantly higher risk (OR = 2.54). Self-reported sleep disorders independently elevated the risk of OAB (OR = 1.46). RCS analysis identified 6 h of sleep as a critical inflection point.ConclusionThis study reveals a U-shaped relationship between sleep duration and the risk of overactive bladder (OAB), with both short (≤ 6 h) and long (≥ 9 h) sleep durations increasing OAB risk. These findings highlight the importance of sleep management in OAB care. Behavioral interventions, including sleep hygiene education and bladder training, may help mitigate symptoms and improve patient outcomes.